2018
DOI: 10.1103/physrevb.97.081105
|View full text |Cite
|
Sign up to set email alerts
|

Balanced electron-hole transport in spin-orbit semimetal SrIrO3 heterostructures

Abstract: Relating the band structure of correlated semimetals to their transport properties is a complex and often open issue. The partial occupation of numerous electron and hole bands can result in properties that are seemingly in contrast with one another, complicating the extraction of the transport coefficients of different bands. The 5d oxide SrIrO 3 hosts parabolic bands of heavy holes and light electrons in gapped Dirac cones due to the interplay between electron-electron interactions and spinorbit coupling. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…The value obtained for this sample at 2 K, n e = 3.0 × 10 20 cm −3 is only weakly temperature dependent (it increases by~6% at room temperature), and is of the same order of magnitude, albeit larger, than the estimate of ref. 23 (n e = 1.6 × 10 20 cm −3 ). Note that the sample of ref.…”
Section: _ω à ámentioning
confidence: 99%
See 3 more Smart Citations
“…The value obtained for this sample at 2 K, n e = 3.0 × 10 20 cm −3 is only weakly temperature dependent (it increases by~6% at room temperature), and is of the same order of magnitude, albeit larger, than the estimate of ref. 23 (n e = 1.6 × 10 20 cm −3 ). Note that the sample of ref.…”
Section: _ω à ámentioning
confidence: 99%
“…Note that the sample of ref. 23 was grown on a different substrate, and that the transport properties have been reported to be substrate dependent 22 . Based on this, and on the assumption that n h~1 .5 × n e (as in ref.…”
Section: _ω à ámentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting bandwidths have been studied through optical spectroscopy, showing an increase from ( ) to ( , ), where in the three-dimensional limit a semimetallic state is found [ 6 ]. Photoemission and transport studies have shown that the unusual electronic structure of (SIO) consists of heavy hole-like and light electron-like bands [ 7 9 ]. First-principles calculations and diffraction measurements show that these electron-like bands originate from Dirac cones that are gapped due to symmetry breaking in response to strain [ 10 ].…”
Section: Introductionmentioning
confidence: 99%